The Influence of Sponsorship on the Stages of the Consumer’s Decision-making Process: A South African Perspective - Sephapo, Catherine Mpolokeng (International Review of Management and Marketing, 2017)
Understanding the consumer’s behaviour is not an easy task; consumers are different and react differently to stimuli. Other factors may influence the consumers’ final decision to purchase a product offering however, literature does not reveal extensive studies that investigated the influence of individual IMC tools on each stage of the consumer decision-making process. The purpose of this study was therefore to explore the influence of sponsorship on the stages of the consumer decision-making process. A qualitative research approach was deemed suitable for the study as it allowed the researcher to understand the thoughts and beliefs of consumers regarding how sponsorship influences their decision-making. A qualitative research approach further allows the researcher to document the experiences of consumers in buying situations and also interpret how consumers make purchasing decisions. A phenomenological research design was applied in this study in order to describe the phenomena; sponsorship; and how it influences the stages of the consumer decision-making process rather than explaining why sponsorship influences these stages. Data for this study was collected by means of naïve sketches and focus groups. The naïve sketches as well as the transcriptions of the focus groups were analysed by means of content analysis. The findings of revealed that sponsorship did not influence consumers’ purchase decisions (the fourth step in the consumer decision-making process) but indicated that sponsorship may play a role in the need recognition, search for alternative and evaluating alternative stages in the consumer decision-making process. Keywords: Consumer behaviour, decision-making process, sponsorship. JEL Classifications: M3, M31